SCMA codebook design based on resource block constellation - Xiaotao SHAO; Mingkun GUO; Wei YANG (Tongxin xuebao)
Aiming at the problems of typical sparse code multiple access codebook design scheme based on multidimensional mother constellation that the complexity is high and the minimum Euclidean distance between constellation points on resource blocks is difficult to determine,a SCMA codebook design scheme based on resource block constellation was proposed.By converting the design of multidimensional mother constellation into the design of two-dimensional resource block constellation,the design complexity of constellation was reduced.And the codebook design scheme starting from resource block constellation could maximize the minimum Euclidean distance between constellation points on resource blocks,which was better than the design method in which user codebooks were obtained from multi-dimensional mother constellation.Simulation results show that the proposed SCMA codebook design scheme based on resource block constellation can significantly improve the BER performance of system compared with the typical codebook design scheme based on multidimensional mother constellation.